2009
DOI: 10.21608/jpp.2009.118802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Methods and Some Weed Control Treatments on Yield and Yield Components of Wheat

Abstract: The aim of the study was to examine the response of wheat cultivar Sakha-93 to 3 weed control treatments and two sowing methods.The experiment included 6 treatments which were the combinations of two sowing methods 1-in ridges 2-rows and response of wheat cultivar Sakha-93 to 3 weed control treatments 1-Unweeded (control) ; 2-Hand weeding twice at 30 and 60 DAS 3-Chemical weed control by Panther 55% Sc at post emergence. The treatments were arranged in split plot design in four replicates, sowing methods in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…The boosting harvest index might be the continued supply of nutrients and higher dry matter distribution towards grain formation provided by the poultry manure treatment combination. This result was in agreement with the investigation of Kabesh et al (2009) and Khan et al (2018).…”
Section: Harvest Indexsupporting
confidence: 94%
“…The boosting harvest index might be the continued supply of nutrients and higher dry matter distribution towards grain formation provided by the poultry manure treatment combination. This result was in agreement with the investigation of Kabesh et al (2009) and Khan et al (2018).…”
Section: Harvest Indexsupporting
confidence: 94%
“…This method seems to be creating favorable conditions around wheat plants such as sufficient water and nutrients supplies, light penetration, CO 2 concentration and other factors affecting wheat growth and development. These results are in agreement with those obtained by Kabesh et al (2009). Increasing seeding rate from 45 to 60 to 75 kg/fed.…”
Section: Wheat Crop 321 Stems Number/msupporting
confidence: 93%
“…However, the difference between ridges and rows was not significant in the 2 nd season (Table 4). Kabesh et al (2009) and Rahman et al (2010) found similar results. Inversely, the wet method produced the least number of spikes in both seasons.…”
Section: Spikes Number/mmentioning
confidence: 52%
“…Sawires (2000) mentioned that application of 100 kg N/fad., gave the highest weight of wheat grains /spike, also Sohail et al (2002), Nassar et al (2004), Abdul Galil et al (2008 Kandil et al (2011) reported that inoculated wheat plants produced higher grain weight compared to non-inoculated plants. The effective role of the dual application of NR 2 Rfixer biofertilizer and chemical N fertilizers was observed on increasing grain weight /spike as recorded by Hassanein and Gomaa (2001), Zaki et al (2007) and Kabesh et al (2009). Phosphorus fertilization regimes influenced significantly wheat grain weight /spike in both seasons and their combined (Table 2).…”
Section: Grain Weight /Spike (G)mentioning
confidence: 73%
“…,Abbasdokht (2008),Badr et al (2009),Kabesh et al (2009),Metin et al (2010),Radwan et al (2013) as well asYousefi and Barzegar (2014), confirmed the meliorating role of biofertilization on 1000-grain weight.…”
mentioning
confidence: 83%